2018
DOI: 10.1159/000500199
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Follow-Up Study on Disclosing Genetic Risk Information (<b><i>APOE</i></b>) to Promote Healthy Lifestyles in Finland

Abstract: <b><i>Aim:</i></b> This observational follow-up study was designed to assess the long-term behavioural and clinical effects of receiving personal genetic risk information. The information disclosed was the carrier status of the apolipoprotein E (<i>APOE</i>)<i></i>alleles, which differentially contribute to the genetic risk for cardiovascular disease (CVD) and Alzheimer’s disease. <b><i>Methods:</i></b> This study forms a continuum with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In line with our findings, previous studies have reported significant positive changes in health behaviour in participants informed of a high ApoE genetic risk in the context of CVD or AD ( Chao et al, 2008 ; Fanshawe et al, 2008 ; Hietaranta-Luoma et al., 2014 , 2018 ; Vernarelli et al, 2010 ). A significant effect of genotype-based personalised nutrition advice has also been reported for genes related to sodium intake ( Nielsen and El-Sohemy, 2014 ) and weight loss ( Arkadianos et al, 2007 ; Vranceanu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our findings, previous studies have reported significant positive changes in health behaviour in participants informed of a high ApoE genetic risk in the context of CVD or AD ( Chao et al, 2008 ; Fanshawe et al, 2008 ; Hietaranta-Luoma et al., 2014 , 2018 ; Vernarelli et al, 2010 ). A significant effect of genotype-based personalised nutrition advice has also been reported for genes related to sodium intake ( Nielsen and El-Sohemy, 2014 ) and weight loss ( Arkadianos et al, 2007 ; Vranceanu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Considering the attrition rate we observed after 10 days it is likely that the study would have been underpowered if the follow-up was extended. Previous studies have demonstrated significant dietary behaviour change 12 months after genebased personalised recommendations (Horne et al, 2020;Nielsen and El-Sohemy, 2014) and in the longest follow-up to date that these changes can be observed more than 5 years after the intervention (Hietaranta-Luoma et al, 2018). The aim of our study was to use genotyping to promote adherence to associated general dietary recommendations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who were interested to participate were sent an information letter containing the study protocol and an overview of the APOE gene. The inclusion criteria have been mentioned in detail in another paper about ApoE4mot project [23].…”
Section: Apoe4mot Project and The Study Participantsmentioning
confidence: 99%
“…No significant differences were noted in the results, but further studies and increased sample size suggested that genetic testing might be useful [15]. In addition, Hanna-Leena et al [14] reported a long-term follow-up study in 2018 on the disclosure of personal genetic risk information (APOE: apolipoprotein E) for cardiovascular diseases to promote a healthy lifestyle in Finland [16]. In conclusion, receiving information on increased personal genetic risk (carrier status of APOE ε4) for cardiovascular diseases provided the motivation for improvements in health behavior.…”
Section: Introductionmentioning
confidence: 99%